THE INFLUENCE OF DISCOVERY LEARNING MODELS ON LEARNING RESULTS THEME 5 SUBTEMA 3 (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
This study aims to determine the effect of the Discovery Learning Model on Learning Outcomes Theme 5 Sub-theme Attitude of Heroism in class IV SDN Lebakwangi in the academic year 2021/2022. This study uses a quantitative research method through a two-group design quasi-experimental approach with Simple Random Sampling. The analytical technique used is the analysis prerequisite test which includes normality test, homogeneity test of variance, and hypothesis testing using t test. The results showed that there was an influence of the Discovery Learning Model on the Learning Outcomes of Theme 5 Sub-theme of Heroic Attitude. This can be seen from the N-Gain in the experimental class group with criteria 83 is very high, while the control class group gets an N-Gain value for criteria 76 is moderate. The completeness of learning outcomes obtained by the experimental group was 100% while in the control class group it was 71%. And the results of hypothesis testing that H0 is rejected and Ha is accepted because Tcount (2.72374) Ttable (2.00030). With this it can be concluded that the research has a positive and significant influence between "The Influence of the Discovery Learning Model on Learning Outcomes Theme 5 Sub-theme 3 Attitude of Heroism is 83 units". The results of this study are expected to provide new knowledge in the application of innovative learning models that can improve learning outcomes.